Preparation and characterization of zinc oxide nanosheets for dye-sensitized solar cell using vitis vinifera dye extraction - Joshi, Leela Pradhan; Subedi, Krishna P; Dangol, Laxmi; Shrestha, Pitamber; Shrestha, Shankar P (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
We have grown Zinc Oxide (ZnO) nanosheet layers on bare glass and conducting Fluorine doped tin oxide (FTO) glass substrates by hydrothermal route.Aluminum doped ZnO (AZO) layer was deposited using a spin coating method prior to growth of ZnO nanostructures which is then used as a seed layer in hydrothermal growth. Asgrown zinc oxide films’ structure, surface morphology and optical properties were studied by using X-ray Diffraction (XRD), Scanning Electron Microscope (SEM) and Ultraviolet Visible (UV-Vis)Spectrophotometer, respectively. XRD study confirmed hexagonal wurtzite structure of ZnO orienting along (002) planes. Scanning Electron Microscope image clearly shows the growth of nanosheet like structures of ZnO. The optical band gap of ZnO film deposited on glass substrate was found to be 3.25eV. We have also studied theinfluence of growth time on band gap of as grown ZnO film grown on FTO coated substrates. Out results showed that the band gap energy was decreased from 3.21eV to 3.16eV for the increase of growth time from 2 hours to 4 hours. We have used Vitis vinifera dye extraction as the natural dye sensitizer in the fabrication of dye-sensitizedsolar cell (DSSC). Our experimental results on I-V measurement of assembled DSSC showed maximum short circuit current and open circuit voltage of about 30 microampers and 600 millivolts, respectively.